The enlightenmentan interpretation: 2: The science of freedom - Gay, Peter (London Wilwood House, 1970)
The Science of Freedom completes Peter Gay's brilliant reinterpretation begun in The Enlightenment: The Rise of Modern Paganism. In the present book, he describes the philosophes' program and their views of society. His masterful appraisal opens a new range of insights into the Enlightenment's critical method and its humane and libertarian vision.